Texas Phoenix Palm Decline - Nigel A. Harrison; Monica L. Elliott (EDIS, 2009)
Revised! PP-243, a 6-page illustrated factsheet by Nigel A. Harrison and Monica L. Elliott, describes this new systemic disease affecting primarily date palms in Florida, the pathogen and hosts, symptoms, diagnostics, and disease management. Includes references. Published by UF Department of Plant Pathology, February 2009.